2021
DOI: 10.1021/acs.energyfuels.0c03881
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Removal Studies of Asphaltene from the Glass Surface

Abstract: Asphaltene deposition in crude oil reservoirs and transportation lines affects the oil recovery and incurs additional operational costs. The current study discusses the removal of asphaltene from inorganic silica surfaces using hydrodynamic forces. The deposition of asphaltene was carried out on clean glass slides (proxy material for silica) from heptane-asphaltene dispersions via aging. For the removal of asphaltene, a parallel plate channel is fabricated with a pocket to place aged substrates under varying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In addition, the size of the asphaltene particles decreases with the increase of Pe (Figure c). Abbas Rizvi et al also found that the size of the asphaltene particles deposited on the surface decreases with the increase of shear rates due to the breakage of asphaltene aggregates.…”
Section: Droplet Formation and Asphaltene Precipitation By Solvent Ex...mentioning
confidence: 93%
“…In addition, the size of the asphaltene particles decreases with the increase of Pe (Figure c). Abbas Rizvi et al also found that the size of the asphaltene particles deposited on the surface decreases with the increase of shear rates due to the breakage of asphaltene aggregates.…”
Section: Droplet Formation and Asphaltene Precipitation By Solvent Ex...mentioning
confidence: 93%
“…The contact measurement was performed using the standard procedure 28,31 sessile drop technique in a Goniometer (model -DSA 100) manufactured by Kruss, Germany. Different sampling liquids, water, and methylene diiodide (MI) were tested on MIP-decorated silica surfaces at 25 C. A droplet of 10 μL of sample solution was placed, and the contact angle was measured by adjusting the drop form to the embedded application.…”
Section: Measurement Of Contact Angle Of Test Liquidsmentioning
confidence: 99%
“…In addition, the testing solutions' surface energy was measured with different silica-modified surfaces. The relationship between the surface energy of the sample solution and the contact angle of test liquids over the surfaces is given by equation (1) 29,31,32…”
Section: Measurement Of Contact Angle Of Test Liquidsmentioning
confidence: 99%
“…It could be further theorized that a functionalized liquid that could act upon these forces, should be able to delay the adsorption . In this regards, Al-sultan et al showed that an anionic surfactant (dodecyl benzenesulfonic acid) could remove efficiently adsorbed asphaltene from stainless steel and glass surfaces at high concentration.…”
Section: Introductionmentioning
confidence: 99%